Paddington in Peru [videorecording (DVD)] - Burton, Mark, 1960-; Foster, Jon, 1984-; Lamont, James, 1982-; King, Paul, 1978-; Farnaby, Simon; Bonneville, Hugh; Mortimer, Emily; Walters, Julie, 1950-; Broadbent, Jim; Harris, Madeleine; Joslin, Samuel; Tous, Carla; et al. (Sony Pictures Home Entertainment, 2025)
Paddington returns to Peru to visit his beloved Aunt Lucy, who now resides at the Home for Retired Bears. With the Brown family in tow, a thrilling adventure ensues when a mystery plunges them into an unexpected journey.